Surgical management of bilateral transmigration of mandibular canines. Case report - Coello de la Cruz, Laurent (2019)
Transmigration is defined as the phenomenon in which an unerupted included tooth transcends the midline by more than half of its length. It is a rare anomaly and it is even more rare to occur bilaterally. It is presented with greater incidence in the mandibular canines, in the female sex, unilaterally, and the left canine being the most commonly affected. The objective of this study is to describe satisfactory surgical management in a 16-year-old asymptomatic male patient, which presented to the intraoral clinical examination absence of both permanent mandibular canines and temporary biscuspid persistence. Lower left, accompanied by a slight dental malposition. In the radiographic exploration (panoramic), both right and left lower canines were observed, in a horizontal position, under the lower incisor apexes. We proceeded to the surgical extraction of both canines, passing the postoperative period without incidents. Satisfactory periodic and radiographic controls were performed at six months.